Effect of mixed hole transporting host on the mobility, Gaussian density of states and efficiencies of a heterojunction phosphorescent organic light emitting diode - Talik N.A.; Woon K.L.; Yap B.K. (Institute of Physics Publishing, 2023)
Blending; Charge injection; Efficiency; Heterojunctions; Hole concentration; Hole traps; Light emission; Light emitting diodes; Molecules; Morphology; Organic light emitting diodes (OLED); Phosphorescence; Semiconductor doping; Doping concentration; Energetic disorder; Film homogeneity; Film morphology; Gaussian density of state; Hole transporting; Phosphorescent organic light emitting diodes; Polyvinylcarbazole; Hole mobility